LSD1 inhibitors from the roots of Pueraria lobata. Issue 1 (2nd January 2023) - Tian, Meng-Ru; Du, Kun; Zhi, Yan-Le; Xue, Gui-Min; Zhao, Zhen-Zhu; Si, Ying-Ying; Chen, Hui; Sun, Yan-Jun; Feng, Wei-Sheng; Ma, Jin-Lian
Abstract: One new 6a, 11a-dehydropterocarpan derivative, 6- O -methyl-anhydrotuberosin (1 ), one new 6a-hydroxypterocarpan, (6a R, 11a R, 11b R )-hydroxytuberosone (7 ), and seven known compounds including two 6a, 11a-dehydropterocarpans (2 and 4 ), two coumestans (3 and 5 ), one isoflavonoid (6 ) and two other phenolic compounds (8 and 9 ) were isolated from the roots of Pueraria lobata . The structures of the isolated compounds were elucidated with spectroscopic and spectrometric methods (1 D and 2DNMR, HRESIMS). Compounds 1, 2, 4 –5 showed potent LSD1 inhibitory activities with IC50 values ranging from 1.73 to 4.99 μM. Furthermore, compound 2 showed potent cytotoxicity against gastric cancer cell lines MGC-803 and BGC-823, and lung cancer cell lines H1299 and H460. Graphical Abstract: UF0001